The role of dermal regeneration template in anterior abdominal wall defect after burst abdomen: A case report in acute graft versus host disease of the gastrointestinal tract in aplastic anemia - Srikanth Vasudevan; Harish Kumar Kabilan; Krithika Jagadish; Y N Anantheswar; Ashok Basur Chandrappa; Dinkar Sreekumar; Annika Marwah (Journal of Indian Association of Pediatric Surgeons, 2022)
Acute graft-versus-host disease of the gastrointestinal tract (GI-aGVHD) is a rare condition, often requiring multiple laparotomies, ultimately leading to a burst abdomen. We report the successful use of a dermal regeneration template (DRT), combined with negative pressure wound therapy (NPWT) and skin grafts, to reconstruct the abdominal skin in an 11-year-old boy. The patient was a case of aplastic anemia, who underwent bone marrow transfers, the first of which failed and the second one was successful. He eventually developed gastrointestinal GVHD. Repeated laparotomies were done for recurrent intestinal obstruction. He also underwent resection anastomosis and end ileostomy, after which he developed an anterior abdominal wall defect due to a burst abdomen. After 12 months of management with multiple dressings, NPWT, and DRT, a stable coverage was achieved, without skin retraction. We report our experience in anterior abdominal wall reconstruction in a case of GI-aGVHD using DRT